ANALISIS TINGKAT KONDISI FISIK PADA ATLET GULAT PUSAT PENDIDIKAN DAN LATIHAN PELAJAR DISPORA RIAU - Br Sitepu, Meliana Kristianai; Vai, Aref; Hidayat, Hirja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the poor physical condition of struggling athletes due to the low training volume, so that they always experience a decrease in physical and technical conditions in competition. The aim of this research was to determine the level of physical fitness of the PPLP Dispora Riau wrestling athletes. The subjects of this research were 6 PPLP Dispora Riau wrestling athletes. This research method uses a research method that must come from field observations through tests. The instruments used are multi-stage fitness test, sit and reach, run 30 meters, run back and forth, hind leg dynamometer. The results of the research (1) Endurance athletes average 72.54 ml/kg/min. (2) arm and shoulder muscle strength averaged 107.08 kg/second. (3) The average amplification rate is 5.386/sec. (4) Flexibility gets 20.85 cm. (5) Agility gets an average of 10.51 seconds. From the recap results of the calculation of the five components of the physical condition of struggling athletes, it was found that 5 athletes consisting of 4 males and 1 female or 83.33% received good categories. Thus, the results of this survey show that the physical condition of the PPLP Dispora Riau wrestling athletes is all in a very good condition.Key Words: Physical fitness, Wrestling